Overcoming Multidrug Resistance in Bacteria Through Antibiotics Delivery in Surface-Engineered Nano-Cargos: Recent Developments for Future Nano-Antibiotics - Yang, Xinfu; Ye, Wenxin; Qi, Yajun; Ying, Yin; Xia, Zhongni (Frontiers in Bioengineering and Biotechnology, 2021)
In the recent few decades, the increase in Multidrug-resistant (MDR) bacteria has reached an ‎alarming rate and caused serious problems. The incidence of infections due to MDR bacteria has ‎been accompanied by morbidity and mortality; therefore, tackling bacterial resistance has become ‎an urgent and necessary task to be processed. The field of nanomedicine has the potential to ‎design and develop efficient antimicrobials for MDR bacteria using its innovative and alternative ‎approaches. The uniquely nanosized antimicrobials have a predominance over traditional ‎antibiotics because the small size of nanosized antimicrobials helps to better interact with cells. ‎Moreover, surface engineering of nanocarriers offers significant advantages of targeting and ‎modulating various resistance mechanisms thus owe superior qualities for overcoming bacterial ‎resistance. This review covers different mechanisms of antibiotic resistance, application of ‎nanocarrier systems in drug delivery, functionalization of nanocarriers, application of ‎functionalized nanocarriers for overcoming bacterial resistance and possible limitations of ‎nanocarriers’ based approach for antibacterial delivery. ‎